Konsep Sakinah sebagai Landasan Pendidikan Anak dalam Keluarga - Muthmainnah, Sari Anthika; Hidayah, Nurul (Jurnal Penelitian Ilmu Ushuluddin, 2024)
The neglect of family as the primary educational environment for children is the root of many issues in the world of education. However, the influence of family on a child's character and education is significant. Disharmony is suspected as the cause of educational failure within families. Utilizing sociological, anthropological, and psychological approaches, this paper aims to explore the concept of education based on the idea of sakinah. Qualitative data collected through library research and analyzed through content analysis is used in this writing. It is found that education based on sakinah will reduce the likelihood of children experiencing trauma, which will have a significant impact on their future, both emotionally and intellectually.